Porphyromonas gingivalis-Host Interactions in a Drosophila melanogaster Model. - Igboin, C.O.; Tordoff, K.P.; Moeschberger, M.L.; Griffen, A.L.; Leys, E.J. (Infection and Immunity, 2011)
Porphyromonas gingivalis is a Gram-negative obligate anaerobe that has been implicated in the etiology of adult periodontitis. We recently introduced a Drosophila melanogaster killing model for examination of P. gingivalis-host interactions. In the current study, the Drosophila killing model was used to characterize the host response to P. gingivalis infection by identifying host components that play a role during infection. Drosophila immune response gene mutants were screened for altered susceptibility to killing by P. gingivalis. The Imd signaling pathway was shown to be important for the survival of Drosophila infected by nonencapsulated P. gingivalis strains but was dispensable for the survival of Drosophila infected by encapsulated P. gingivalis strains. The P. gingivalis capsule was shown to mediate resistance to killing by Drosophila antimicrobial peptides (Imd pathway-regulated cecropinA and drosocin) and human beta-defensin 3. Drosophila thiol-ester protein II (Tep II) and Tep IV and the tumor necrosis factor (TNF) homolog Eiger were also involved in the immune response against P. gingivalis infection, while the scavenger receptors Eater and Croquemort played no roles in the response to P. gingivalis infection. This study demonstrates that the Drosophila killing model is a useful high-throughput model for characterizing the host response to P. gingivalis infection and uncovering novel interactions between the bacterium and the host.